Comparison of endoscopic findings in Egyptian and Indian patients: a retrospective cohort - Essam A Hassan; Tarek I Ahmed; Sanjay Rajput (Wolters Kluwer Medknow Publications, 2019)
Aims Esophagogastroduodenoscopy is the commonest diagnostic procedure performed to evaluate upper gastrointestinal tract. However, there are limited data on the differences in endoscopic findings in different populations. Therefore, we conducted this study to compare the frequencies of endoscopic findings in two different populations. Patients and methods We used a large endoscopic database to retrieve the data of patients who underwent esophagogastroduodenoscopy at Fayoum University Hospital, Egypt and Ansh Clinic, Ahmadabad, India in the year of 2016. Results A total of 7107 patients were included in the final analysis: 5527 from India and 1580 from Egypt. Indian patients were more likely to present with normal finding (54.6 vs. 22.7%, P<0.001), whereas Egyptian patients were presenting with varices more commonly (49.5 vs. 15.9%, P<0.001). The Egyptian cohort showed a high frequency of grades I and III gastroesophageal reflux disease, whereas the Indian cohort revealed higher grades I and II varices (P<0.001). Gastritis was more common in Indian patients (67.2 vs. 35.2%, P>0.001). Overall, varices are most common in older male patients (>20 years), gastroesophageal reflux in males, and gastritis in females. Conclusion Further research is needed to validate our findings regarding the effect of age and sex on the frequency of endoscopic findings.